Stretching, Shaking, Inflating: Volcanic-Tectonic Interactions at a Rifting Silicic Caldera - Muirhead, James D.; Illsley-Kemp, Finnigan; Barker, Simon J.; Villamor, Pilar; Wilson, Colin J. N.; Otway, Peter; Mestel, Eleanor R. H.; Leonard, Graham S.; Ellis, Susan; Savage, Martha K.; Bannister, Stephen; Rowland, Julie V.; et al. (Frontiers in Earth Science, 2022)
Silicic caldera volcanoes are frequently situated in regions of tectonic extension, such as continental rifts, and are subject to periods of unrest and/or eruption that can be triggered by the interplay between magmatic and tectonic processes. Modern (instrumental) observations of deformation patterns associated with magmatic and tectonic unrest in the lead up to eruptive events at silicic calderas are sparse. Therefore, our understanding of the magmatic-tectonic processes associated with volcanic unrest at silicic calderas is largely dependent on historical and geological observations. Here we utilize existing instrumental, historical and geological data to provide an overview of the magmatic-tectonic deformation patterns operating over annual to 104 year timescales at Taupō volcano, now largely submerged beneath Lake Taupō, in the rifted-arc of the Taupō Volcanic Zone. Short-term deformation patterns observed from seismicity, lake level recordings and historical records are characterized by decadal-scale uplift and subsidence with accompanying seismic swarms, ground shaking and surface ruptures, many of which may reflect magma injections into and around the magma reservoir. The decadal-scale frequency at which intense seismic events occur shows that ground shaking, rather than volcanic eruptions, is the primary short-term local hazard in the Taupō District. Deformation trends near and in the caldera on 101–104 yr timescales are atypical of the longer-term behavior of a continental rift, with magma influx within the crust suppressing axial subsidence of the rift basin within ∼10 km of the caldera margin. Examination of exposed faults and fissures reveals that silicic volcanic eruptions from Taupō volcano are characterized by intense syn-eruptive deformation that can occasionally extend up to 50 km outside the caldera structure, including ground shaking, fissuring and triggered fault movements. We conclude that eruption and unrest scenarios at Taupō volcano depend on the three-way coupling between the mafic-silicic-tectonic systems, with eruption and/or unrest events leading to six possible outcomes initially triggered by mafic injection either into or outside the magma mush system, or by changes to the tectonic stress state.